Knowledge Sharing Mechanism of the TOS - Shah, Abad A.; Fotouhi, Farshad; Grosky, William (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1994)
In [5], [10] we proposed TOS: A Temporal Object System that handles the structure and stature changes in an object in a uniform and temporal fashion. The TOS takes a hybrid approach of c class-based and prototype-based approaches that makes it more flexible than other no approaches. In this paper, we propose a formal model for knowledge sharing mechanism (Share-kno) for hierarchy af objects of the TOS, and formally prove that the mechanism (Share-kno) encapsulate more knowledge than inheritance and delegation models which are proposed by Stein in [12].